Influence of Intervention Method And Intelligence to Ability Centralization Children With Attention Deficit Hyperactive Disorder In Inclusive Basic School - Endang Sutisnowati; Martini Jamaris; Mulyono Abudurrahman (Journal of Development Research, 2019)
Conceptually the problem of education for children with special needs and special services in the setting of inclusive education is the actual problem that is needed now. Many developmental disorders that begin in infancy and can continue into adulthood. Disorders of children who can not concentrate is a multifactoral status disorder. Inclusive education is expected to solve one problem in handling the education of children with disabilities, especially children with impaired concentration and hyperactivity, or often known as ADHD. This study aims to determine and measure empirical data about differences in the ability of focus concentration of Attention Deficit Hyperactivity Disorder (ADHD) children who are treated with the Back in control method and the Lovaas method, by paying attention to the intelligence of students in grades 1 and 2 at Bojongrenget State Elementary School II Tangerang (Inclusive school). The basic problem in this study, is the concentration of ADHD children, therefore this study uses the method of intervention modification of Back in Control and Lovaas method with 2x2 factorial design experiments. Conclusion of Hypothesis testing, there is also a very significant interaction effect between the method of intervention Back in Control, Lovaas and intelligence on the ability to focus concentration on children with ADHD, so that a simple effect occurs, a further test (tukey test) occurs. T test results can be concluded, ADHD children with high intelligence have better concentration ability when given treatment with the Back in Control method, than Lovaas method treatment. ADHD children with low intelligence have better concentration ability using Lovaas method treatment, than Back in Control method. Thus there is a significant difference between the ability of concentration with the treatment of the Back in Control method and the Lovaas method.